Thermohydraulic characteristics of a multi-string direct-contact heat exchanger. (November 2018) - Zeng, Zezhi; Sadeghpour, Abolfazl; Ju, Y. Sungtaek
Highlights: Multi-string heat exchangers have been successfully demonstrated. Flow instability can reduce liquid-side thermal resistance. Data demonstrate applicability of the Reynolds analogy. Abstract: Direct-contact heat exchangers that involve energy exchange between gas and liquid streams have a variety of applications, including waste heat recovery, thermoelectric power plant cooling, and thermal desalination. Direct-contact heat exchangers are appealing as they may help mitigate potential corrosion, fouling, and scaling of solid surfaces and enhance heat transfer effectiveness. In this study, we experimentally investigate the thermohydraulic characteristics of an economic light-weight direct-contact heat exchanger that incorporates an array of strings of diameter of the order of 0.1–1 mm to sustain flows of thin liquid films. We constructed a 1.6 m-tall prototype heat exchanger with an array of as many as 112 vertically aligned strings. Thin films of a non-evaporating liquid are flown down the strings by gravity and exchange thermal energy with a counterflowing gas stream. We obtained axial liquid temperature profiles and frictional loss in the gas stream for different combinations of liquid and gas flow rates and two different string pitches. Numerical simulation is also performed to help interpret and indirectly validate our experimental results. The overall, gas-side, and liquid-side heat transfer coefficients extracted from the experimentally measured temperature profiles are examined to evaluate the impact of instability in liquid film flows and inter-bead spacing. The applicability of the Reynolds analogy is also assessed using the measured gas-stream pressure drops and air-side heat transfer coefficients. The present study helps improve our understanding of heat transfer and gas-stream pressure drop in string-based direct-contact heat exchangers and provides an experimental database to help systematically optimize their design.